2014
DOI: 10.1007/s10195-014-0309-8
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying tendinitis of the rotator cuff after arthroscopic excision of calcium deposits: report of two cases and literature review

Abstract: Ossifying tendinitis (OT) is a type of heterotopic ossification, characterized by deposition of hydroxyapatite crystals in a histologic pattern of mature lamellar bone. It is usually associated with surgical intervention or trauma and is more commonly seen in Achilles or distal biceps tendons, and also in the gluteus maximus tendon. To our knowledge, there is no description of OT as a complication of calcifying tendinitis of the rotator cuff. In this report, we describe two cases in which the patients develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Patients with knee pain secondary to fabella report tenderness and pain in the PLC of the knee and a grating sensation during knee motion. [18,19]…”
Section: Discussionmentioning
confidence: 99%
“…Patients with knee pain secondary to fabella report tenderness and pain in the PLC of the knee and a grating sensation during knee motion. [18,19]…”
Section: Discussionmentioning
confidence: 99%
“…Three studies involving 13 patients reported on HO within the subacromial space, subdeltoid fascia, and supraspinatus tendon after subacromial decompression. 10,39,49 All patients presented with impingement symptoms, with 11 patients experiencing pain resolution after revision arthroscopic decompression. Severe HO after arthroscopic acromioplasty in a 48-year-old man at 22-month follow-up has been reported, with bony bridging of the acromion to the humerus.…”
Section: Ho After Arthroscopy Outside the Hip: Management Outcomesmentioning
confidence: 99%
“…During surgery to alleviate the pain of refractory calcific tendinitis, calcium removal was performed under a mini-open approach, and there may have been damage to soft tissues and decreased blood flow. Although two cases of minor HO in the insertion of the rotator cuff after calcific tendinitis have been reported in the literature, 13) to the best of our knowledge, there have been no reports of a massive HO as described in the present case. Periarticular HO of the shoulder has been previously reported, and there have been numerous reports on HO after hemi-, total-, or reverse-shoulder arthroplasty.…”
Section: Discussionmentioning
confidence: 48%